Production and physical composition of Priangan male sheep carcass supplemented by Pasak Bumi peptide (Eurycoma longifolia Jack) - Zubir .; R. Priyanto; E. Gurnadi; W. Manalu; H.M. Winugroho (Indonesian Center for Animal Research and Development (ICARD), 2011)
Pasak Bumi (Eurycoma longifolia Jack/ELJ) is frequently claimmed to increase expression of masculinity, including inducing the lean growth. This study was aimed to determine the effect of ELJ peptide supplementation on yield and physical composition of lamb carcasses. Sixteen Priangan rams about 1 year old with average weight of 30.43±1.41 kg were maintained in individual cages. The experimental rams were divided into 4 treatments i.e. T0, T1, T2, and T3. In T0, T1 and T2 treatments, the experimental rams were administered: 0, 1.5, and 3 mg ELJ peptide/kg BW, respectively. In the T3 treatment, the experimental ram were administered 1 mg/kg commercial product eurypeptide®. The ELJ peptide and commercial product were administered first in the morning prior to feeding. The experiment was conducted in a completely randomized design of four treatments and four replications. Data were covariance analyzed with an empty body weight as covariate for carcass weight and the right carcass weight as covariate for carcasses physical composition. The results showed that the weights of dissection body fat of T2 and T3 were lower than T0 (P < 0.05) and T1 (P < 0.01). Fat weight reduction was found in all parts of the carcass and more apparent in the fore saddle. Lean weights were higher ( P < 0.05) in T3 and T2 as compared to T1 and T0. The pattern of lean weight differed among treatments in the wholesale cuts that follow the total lean weight eventhough it was not significant. ELJ peptide treatment did not significantly affect either bone weight or wholesale cuts weight. In conclusion, T2 and T3 can improve carcass composition with equal ability. Key Words: Ram, Eurycoma Longifolia Peptide, Carcass